Molecular identification and anticancer activity of alkylphenol from cashew nut shell oil (Anacardium occidentale) grown In Timor Island - Antonius R B Ola; Zullies Ikawati; Sismindari .; Ermelinda D Meye; Bibiana Dho Tawo (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Isolation of anacardic acid and cardanol from cashew nut shell liquid and their cytotoxic activity to on ward HeLa cancer cell line has been done. The objective of this research is to isolate and identify anacardic acid and cardanol from CNSL along with their cytototoxic activity towards HeLa cancer cell lines. Anacardic acid was isolated as calcium anacardate. Hydrolisis of this acid with acid chloride yields anacardic acid . Liquor ammonia was added to the acid-free CNSL and extracted with hexane/ethyl acetate (98:2) to isolate cardanol and with ethyl acetate/hexane (80:20) to separate cardol. Cardanol was obtained as the main chemical component of CNSL derived from Kupang district. Anacardic acid and cardanol was analyzed using IR and GC-MS. Anticancer activity of chemical components of CNSL against HeLa cancer cell lines were studied using MTT. Cytotoxic activity test showed that CNSL, anacardic acid and cardanol can be developed as anticancer agent.Key words : CNSL, anacardic acid, cardanol, anticancer.